Pre-service Geography Teachers' Technological Pedagogical Content Knowledge (TPACK) Proficiency: A Student Perspective - Urfan, Faiz; Sari, Rima Meilita; Akbari, Myrza (Department of Geography Education, University of Jember, 2025)
Students should be the primary beneficiaries of teachers' TPACK proficiency. This study aimed to investigate the proficiency of pre-service geography teachers in Technological Pedagogical Content Knowledge (TPACK) through the lens of student perceptions. TPACK, a framework that integrates technological, pedagogical, and content knowledge, is crucial for effective teaching in the digital age. By understanding students' perceptions, this research sought to identify areas where pre-service teachers excel and where they might need further development. The respondents of this research were public high school (Sekolah Menengah Atas Negeri/SMAN) students from Langsa City, Aceh Province. The number of respondents involved was 184 students. They came from SMAN 2 Langsa, SMAN 4 Langsa, and SMAN 5 Langsa where the pre-service teacher was placed during their teaching practice. The research method used is quantitative descriptive based on a questionnaire which aims to measure TPACK proficiency in pre-service geography teachers according to student perception. The results of the study showed that pre-service teachers' TPACK proficiency was very good based on the respondents' perspectives, especially in the aspects of pedagogy and geography content knowledge. However, technological knowledge has results at the good level, which is lower than the other two aspects. Based on these results, the recommendation offered is that the technological capabilities of pre-service geography teachers should to be improved to provide a better learning experience for students.